2012
DOI: 10.1016/j.bbamem.2012.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric liposome particles with highly efficient encapsulation of siRNA and without nonspecific cell penetration suitable for target-specific delivery

Abstract: The discovery of siRNA has been an important step in gene therapy, but the problem of delivering siRNA to a target organ limits its use as a therapeutic drug. Liposomes can be used as a nonviral vector to deliver siRNA to target cells. In this study we developed a novel method of producing asymmetric liposome particles (ALPs) with highly efficient siRNA encapsulation. Two kinds of lipid inverted micelles were prepared for the purpose of obtaining ALPs. The inner one is composed of ionizable cationic 1,2-dioleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 38 publications
1
36
0
Order By: Relevance
“…For certain diseases, such as cancer, passive targeting based on an enhanced permeation and retention effect can increase tumor drug accumulation [113], however, the improvement is often moderate. Therefore, siRNA nanocarriers developed in recent years have often been functionalized with active-targeting moieties, such as mono-clonal antibodies, receptor substrates and cell-penetrating peptides [90,114116]. The advantage of this active-targeting strategy is illustrated in the study of asymmetric liposome particles, which were designed with the positive charges on the inner surface to minimize the nonspecific cellular uptake [114].…”
Section: Strategies To Overcome Nanotoxicity Of Sirna Carriersmentioning
confidence: 99%
See 1 more Smart Citation
“…For certain diseases, such as cancer, passive targeting based on an enhanced permeation and retention effect can increase tumor drug accumulation [113], however, the improvement is often moderate. Therefore, siRNA nanocarriers developed in recent years have often been functionalized with active-targeting moieties, such as mono-clonal antibodies, receptor substrates and cell-penetrating peptides [90,114116]. The advantage of this active-targeting strategy is illustrated in the study of asymmetric liposome particles, which were designed with the positive charges on the inner surface to minimize the nonspecific cellular uptake [114].…”
Section: Strategies To Overcome Nanotoxicity Of Sirna Carriersmentioning
confidence: 99%
“…Therefore, siRNA nanocarriers developed in recent years have often been functionalized with active-targeting moieties, such as mono-clonal antibodies, receptor substrates and cell-penetrating peptides [90,114116]. The advantage of this active-targeting strategy is illustrated in the study of asymmetric liposome particles, which were designed with the positive charges on the inner surface to minimize the nonspecific cellular uptake [114]. Only after decorating asymmetric liposome particles with anti-EGFR could receptor-mediated uptake into lung cancer cell lines but not into the EGFR-free NIH-3T3 cells be effectively induced.…”
Section: Strategies To Overcome Nanotoxicity Of Sirna Carriersmentioning
confidence: 99%
“…target-specific drug delivery to an intended lesion. [5][6][7][8][9] Encapsulation of bio-active substances with liposome or polymer nanoparticles as well as rearrangement of active molecules within inorganic nanomaterials have been tried to achieve enhanced transportation efficacy and modified release. 10 11 Among various nanomaterials, layered inorganics such as layered double hydroxides (LDHs) and clays have attracted increasing interests due to their unique 2-dimensional structures which can modulate the molecular arrangement of payload resulting in enhanced stability and controlled release property.…”
Section: Introductionmentioning
confidence: 99%
“…23 This blocks the phosphorylation and activation of receptor-associated tyrosine kinases, leading to tumoricidal effects. 24 Preclinical studies have demonstrated growth suppression of EGFR-overexpressing tumors. 25-28 …”
Section: Introductionmentioning
confidence: 99%